Koordinasi Aktor Dalam Pembangunan Perusahaan Dalam Kerjasama Dengan Pihak Eksternal (Studi Kasus: PT Pratama Jatim Lestari) - Wardani, Danastri Putri; Hardjati, Susi (Universitas Pahlawan Tuanku Tambusai, 2024)
Coordination of actors allows companies to implement cohesive and integrated strategies. Through collaboration and effective communication between internal actors, companies can reach mutual agreement on strategic direction, resource allocation, and action priorities. Actor coordination plays a crucial role in company development through collaboration with external parties. As is the case at PT Pratama Jatim Lestari. PT. Pratama Jatim Lestari is a new company operating in the field of hazardous and toxic waste management. Because PT Pratama Jatim Lestari is still at the factory construction stage, it is certain that the company cannot build the factory alone and/or without assistance from other parties. Therefore, collaborating with other companies to carry out factory construction is something that must be done by PT Pratama Jatim Lestari. The aim of this research is to create an actor coordinator in company development in collaboration with external parties. The research method used is a qualitative descriptive approach. Primary data sources are the results of observations, interviews and documentation. The data collection technique uses in-depth interviews, this technique is used to dig up more information that will be used for research results. The research results show that the actor coordinator in company development is categorized as good. This process is going well with the aim of achieving the goals that have been set in accordance with what Hasibuan, also said that coordination is an activity of directing, integrating and coordinating management elements and the work of subordinates in achieving goals. Organization.